Al borde : integración de sistemas (2018)
"The project consists in restructuring La Cañiza,  a neighborhood located on the northwestern side of the Tibabuyes wetland, through a progressive hybrid edge system that aims to improve the urban, housing quality standards and integrate the wetland with the urban fabric of the neighborhood. The project works from the urban to the landscape scale and has a development in the temporal continuum determined by the dynamics of the sector. This new border reinterprets the physical structure and takes advantage the existing social dynamics. The restructuring is based on the progressive development of a new predial structure that arises from the existing one. The project attends a population density issue giving solution through better social housing conditions without promoting the gentrification of the neighborhood. On an urban scale, the new prediality aims to strengthen the conditions that generate diversity by qualifying housing use, promoting commercial dynamics and introducing cultural and institutional uses. Thus, the new urban fabric aims through concentration and combination of uses to generate a mixed and active border that responds to the natural system that adjoins the neighborhood. The interlace between the natural system and the urban structure occurs through the entrance of hydraulic and vegetal channels of different scales strategically located, this new relationship aims to invigorate life among the buildings and generate a gradation among the public, communal and private spaces. Thus, the aim is to restore the natural cycle of water for the benefit of the community and to reclaim its role in the social construction of the landscape."--Tomado del Formato de Documento de Grado.